Wayang Edu: digital application for Wayang Kulit Kelantan - Fara Dayana Mohd Jufry, Nor Masharah Binti Husain, Mohammad Naquiddin Tajul Ariffin (Tanjung Malim, 2024)
Wayang Edu: digital application for Wayang Kulit Kelantan by Fara Dayana Mohd Jufry, Nor Masharah Binti Husain, Mohammad Naquiddin Tajul Ariffin